2022
DOI: 10.24908/pocus.v7i1.15019
|View full text |Cite
|
Sign up to set email alerts
|

Near Peer POCUS Education Evaluation

Abstract: Objective: At Texas College of Osteopathic Medicine (TCOM), point of care ultrasound (POCUS) is taught to medical students in conjunction with trained medical student teaching assistants (TAs). The purpose of our study is to evaluate the effectiveness of near peer teaching in the setting of ultrasound education. We hypothesized that this would be the preferred learning technique among TCOM students and TAs.  Methods: To evaluate our hypotheses about the value of near peer instruction, we created two comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…POCUS is an invaluable tool for pediatric specialists to enhance diagnostic accuracy and patient satisfaction. It is rapidly and easily learnt, even by medical students [17]. Therefore, it is crucial for pediatric residents to incorporate it into their routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…POCUS is an invaluable tool for pediatric specialists to enhance diagnostic accuracy and patient satisfaction. It is rapidly and easily learnt, even by medical students [17]. Therefore, it is crucial for pediatric residents to incorporate it into their routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…POCUS is an invaluable tool for pediatric specialists to enhance diagnostic accuracy. It is rapidly and easily learnt, even by medical students [ 17 ]. Therefore, it is crucial for pediatric residents to incorporate it into their routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…To further address the lack of instructors, SCPEC attendees recommended using near-peer instruction (NPI), whereby medical students who have a special interest or training in POCUS are able to instruct their peers. Schools capitalizing on NPI have been able to reduce the teaching load placed on faculty 29 , 30 , 31 , 32 , 33 .For example, Hendriksz et al demonstrated that only 2 hours of faculty time was required to train a peer mentor to an acceptable level of expertise for a particular teaching session 29 . Similarly, a randomized controlled trial showed that student-mentors, trained with short teaching intervals and self-directed learning, could be taught to instruct musculoskeletal ultrasound at a level similar to faculty 34 .…”
Section: Discussionmentioning
confidence: 99%